Detailed cytogenetic analysis of three duck species (the northern pintail, mallard, and common goldeneye) and karyotype evolution in the family Anatidae (Anseriformes, Aves) - V. R. Beklemisheva; K. V. Tishakova; S. A. Romanenko; D. A. Andreushkova; V. A. Yudkin; E. А. Interesova; F. Yang; M. A. Ferguson-Smith; A. S. Graphodatsky; A. A. Proskuryakova (Вавиловский журнал генетики и селекции, 2024)
Galliformes and Anseriformes are two branches of the Galloanserae group, basal to other Neognathae. In contrast to Galliformes, Anseriformes have not been thoroughly researched by cytogenetic methods. This report is focused on representatives of Anseriformes and the evolution of their chromosome sets. Detailed cytogenetic analysis (G-banding, C-banding, and fluorescence in situ hybridization) was performed on three duck species: the northern pintail (Anas acuta, 2n = 80), the mallard (A. platyrhynchos, 2n = 80), and the common goldeneye (Bucephala clangula, 2n = 80). Using stone curlew (Burhinus oedicnemus, 2n = 42, Charadriiformes) chromosome painting probes, we created homology maps covering macrochromosomes and some microchromosomes. The results indicated a high level of syntenic group conservation among the duck genomes. The two Anas species share their macrochromosome number, whereas in B. clangula, this number is increased due to fissions of two ancestral elements. Additionally, in this species, the presence of massive heterochromatic blocks in most macroautosomes and sex chromosomes was discovered. Localization of clusters of ribosomal DNA and telomere repeats revealed that the duck karyotypes contain some microchromosomes that bear ribosomal RNA genes and/or are enriched for telomere repeats and constitutive heterochromatin. Dot plot (D-GENIES) analysis confirmed the established view about the high level of syntenic group conservation among Anatidae genomes. The new data about the three Anatidae species add knowledge about the transformation of macro- and sex chromosomes of Anseriformes during evolution.